Comparison of Response, Hard Work Character and Character of Love for the Motherland of Students: Integration of Traditional Games Patok Lele - Syahrial Syahrial; Asrial Asrial; Arsil Arsil; Silvina Noviyanti; Dwi Agus Kurniawan; M. Andika Robiansah; Qonita Luthfiah (STAI Hubbulwathan Duri, 2021)
This study aimed to see the effect of integrating the traditional Game of Patok Lele on learning. This type of research is a mixed method. This study involved several variables as research categories, namely response, cooperative character, and peace-loving character, with a sample of 50 students. Data analysis used descriptive and inferential statistics. The integration was carried out at the State Elementary School 45/I Sridadi and Madrasah Ibtidaiyah 1 Batang Hari seen in the response, the character of cooperation and the character of love for the homeland. The result is that each variable of the response, social care character, and patriotism character has a significant comparison, with a value of sig 0.05 and each dominant variable in the good category.